Immunoreactive calcitonin in leukaemia. Issue 6202 (1st December 1979) - Hillyard, C J; Oscier, D G; Foa, R; Catovsky, D; Goldman, J M
Abstract : A radioimmunoassay was used to measure concentrations of immunoreactive human calcitonin (HCT) in plasma and leucocytes from patients with various leukaemic and myeloproliferative disorders. Plasma immunoreactive HCT concentrations were increased in 32 out of 33 patients with chronic granulocytic leukaemia (CGL) and in all eight patients with acute myeloid leukamia (AML) at presentation or in relapse. Out of 11 patients with other myeloproliferative disorders, eight had increased plasma immunoreactive HCT concentrations. Buffy-coat-cell extracts and culture media from peripheral leucocytes of patients with CGL also contained increased immunoreactive HCT concentrations. In contrast, plasma from patients with chronic lymphocytic leukaemia, acute lymphoblastic leukaemia, and AML in remission had low or undetectable immunoreactive HCT concentrations. Increased plasma and cellular concentrations of immunoreactive HCT may be a consequence of abnormal proliferation of myeloid cells and might prove to be valuable in predicting relapse in patients with myeloid leukaemias.